BIOMECHANICAL DIFFERENCES BETWEEN CASES WITH CECS AND ASYMPTOMATIC CONTROLS DURING RUNNING. Issue 22 (1st November 2016) - Roberts, A; Roscoe, D; Hulse, D; Bennett, A; Dixon, S
Abstract : Chronic exertional compartment syndrome (CECS) presents as exertional pain in the lower limb as a result of elevation of intramuscular compartment pressure. Treatment of CECS through a change in running style has recently been suggested to improve symptoms however no primary research has investigated whether patients with CECS run differently to controls. This study aimed to compare the kinematic differences in cases with CECS and controls. 20 men with symptoms of CECS of the anterior compartment and 20 asymptomatic male controls participated. Barefoot and shod running 3D kinematics; and anthropometry were compared. Cases were heavier than controls with no differences in height. This result contrasts with our recent study that reported that cases in that cohort were on average 10 cm shorter than controls; with no differences in weight. As such we have previously suggested that small stature may be a risk factor for CECS in the military. Further work is now needed to provide more robust data on this theory. Our findings are the first to demonstrate that CECS patients run with a different gait pattern to controls. Cases displayed less anterior trunk lean and less anterior pelvic tilt throughout the whole gait cycle and a more upright shank inclination angle during late swing. Cases demonstrated greater step length and stance time, although this was not consistent across conditions. Alterations to running style that have been used in an attempt to reduce the anterior compartment activity of CECS patients typically encouraged greater forward lean; along with other more distal changes. Clinical observations have also suggested increased ankle dorsiflexion and reduced heel lift during swing phase. The differences reported in this study only partially match the anecdotal observations previously described in the literature. However, no consistent differences were found at the ankle joint. Our results therefore demonstrate the importance of acquiring higher level evidence before implementing gait re-education programs. Assuming the reported interventions reduce anterior compartment muscle activity, they may simply modify activity, rather than changing pathological gait. The longer stride length is a continuing theme in this population and as such we believe this may be a key component in the development of the condition.